PENGEMBANGAN MEDIA “SI DATU” PADA PELAJARAN IPAS TOPIK “BAGIAN TUBUH TUMBUHAN” KELAS IV SEKOLAH DASAR - Kolifatun Nisa; M. Yusuf Setia Wardana; Veryliana Purnamasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The goals of this study are threefold: first, to assist in the creation of the media "Si Datu" for use in the Science Lesson "Parts of Plants" in Fourth Grade Elementary School; second, to assess the media's usefulness in this context; and third, to collect feedback from both teachers and students on this topic. This study employs a method of research and development (R&D) that is often used in the manufacturing and validation of various goods. Analyse, Design, Develop, Implement, and Evaluate is the acronym for the ADDIE approach that this research follows. The study on the media "Si Datu" in the Science Lesson Topic "Parts of Plants" Grade IV that was produced yielded valid findings with an average validation percentage of 98% from media specialists. As compared to the 93% achieved by the subject matter expert. Further, 86% of fourth grade instructors and 98% of fourth graders responded to the survey. The study findings indicate that the creation of the "Si Datu" learning medium falls under the "Very Appropriate" category and is suitable for use in the classroom. Keywords: Learning Media, Android, Ispring Suite